SARS-CoV-2 infection of human ACE2-transgenic mice causes severe lung inflammation and impaired function - Winkler, Emma S.; Bailey, Adam L.; Kafai, Natasha M.; Nair, Sharmila; McCune, Broc T.; Yu, Jinsheng; Fox, Julie M.; Chen, Rita E.; Earnest, James T.; Keeler, Shamus P.; Ritter, Jon H.; Kang, Liang-I; et al. (Nature immunology, 2020)
Although animal models have been evaluated for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, none have fully recapitulated the lung disease phenotypes seen in humans who have been hospitalized. Here, we evaluate transgenic mice expressing the human angiotensin I-converting enzyme 2 (ACE2) receptor driven by the cytokeratin-18 (K18) gene promoter (K18-hACE2) as a model of SARS-CoV-2 infection. Intranasal inoculation of SARS-CoV-2 in K18-hACE2 mice results in high levels of viral infection in lungs, with spread to other organs. A decline in pulmonary function occurs 4 days after peak viral titer and correlates with infiltration of monocytes, neutrophils and activated T cells. SARS-CoV-2-infected lung tissues show a massively upregulated innate immune response with signatures of nuclear factor-κB-dependent, type I and II interferon signaling, and leukocyte activation pathways. Thus, the K18-hACE2 model of SARS-CoV-2 infection shares many features of severe COVID-19 infection and can be used to define the basis of lung disease and test immune and antiviral-based countermeasures. Diamond and colleagues generate a K18-hACE2 model of SARS-CoV-2 infection that shares many features of severe COVID-19 infection and can be used to define the basis of lung disease and test immune and antiviral-based countermeasures.